Seroepidemiological Reconstruction of Long-term Chikungunya Virus Circulation in Burkina Faso and Gabon. (17th June 2022) - Lim, Jacqueline Kyungah; Ridde, Valery; Agnandji, Selidji Todagbe; Lell, Bertrand; Yaro, Seydou; Yang, Jae Seung; Hoinard, Damien; Weaver, Scott C; Vanhomwegen, Jessica; Salje, Henrik; Yoon, In-Kyu
Abstract: Chikungunya virus (CHIKV) is a major public health concern worldwide. However, infection levels are rarely known, especially in Africa. We recruited individuals from Ouagadougou, Burkina Faso and Lambaréné, Gabon (age range, 1–55 years), tested their blood for CHIKV antibodies, and used serocatalytic models to reconstruct epidemiological histories. In Ouagadougou, 291 of 999 (29.1%) individuals were seropositive, ranging from 2% among those aged <10 years to 66% in those aged 40–55 years. We estimated there were 7 outbreaks since the 1970s but none since 2001, resulting in 600 000 infections in the city, none of which were reported. However, we could not definitively conclude whether infections were due to CHIKV or o'nyong-nyong, another alphavirus. In Lambaréné, 117 of 427 (27%) participants were seropositive. Our model identified a single outbreak sometime since 2007, consistent with the only reported CHIKV outbreak in the country. These findings suggest sporadic outbreaks in these settings and that the burden remains undetected or incorrectly attributed. Abstract : We conducted chikungunya virus serostudies and used models to reconstruct past circulation. In Burkina Faso, we identified 7 outbreaks, compared to a single outbreak in Gabon. Serostudies with models have a key role in supporting disease surveillance.